Increase of jump performance during GH treatment in short children born SGA - Schweizer, Roland; Martin, David D.; Binder, Gerhard (Frontiers in Endocrinology, 2023)
Background: Short children born small for gestational age (SGA) often have low muscle mass. Studies on maximal isometric grip-force (MIGF) observed lower muscle strength in these children. In contrast to MIGF, jumping is an everyday muscle activity for children. Our hypothesis was that GH treatment would cause an increase in jumping strength. So, we aimed to study jumping by mechanography in short SGA children before and during GH treatment. Methods: Monocentric prospective longitudinal study in a tertiary paediatric endocrinology centre. We studied 50 prepubertal short children (23 females) born SGA (mean age 7.2 y, height -3.24 SDS) during GH treatment (mean dose 45 µg/kg/d). Main outcome measures were Peak jump force (PJF) and peak jump power (PJP) measured by Leonardo® ground reaction force plate at baseline and after 12 months of GH treatment. Mechanography data were compared to sex, age and height related references (SD-Score). Fitness was estimated as PJP/kg body weight by use of the Esslinger-Fitness-Index (EFI). Results: At start of GH treatment PJP/body weight was low at -1.52 SDS and increased significantly to -0.95 SDS during 12 months of treatment (p<0.001). PJF was low-normal compared to height dependent references and remained unchanged. PJP was normal compared to height dependent references and increased only slightly from -0.34 to -0.19 SDSHT. Conclusions: Jumping performance (EFI) measured by mechanography increased during one year of GH treatment in short children born SGA.